2017
DOI: 10.1186/s12864-016-3441-4
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of the mosquito Aedes fluviatilis (Diptera: Culicidae), and transcriptional changes associated with its native Wolbachia infection

Abstract: Background Wolbachia is a bacterial endosymbiont that naturally infects a wide range of insect species, and causes drastic changes to host biology. Stable infections of Wolbachia in mosquitoes can inhibit infection with medically important pathogens such as dengue virus and malaria-causing Plasmodium parasites. However, some native Wolbachia strains can enhance infection with certain pathogens, as is the case for the mosquito Aedes fluviatilis, where infection with Plasmodium gallinaceum is enhanced by the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 106 publications
2
56
0
Order By: Relevance
“…However, both the insects with newly acquired Wolbachia infection and those insects that have been infected by Wolbachia naturally for a long time, increase their resistance to pathogens (Kambris et al, 2009;Moreira et al, 2009;Pan et al, 2018). Furthermore, some studies, including our group, found that Wolbachia significantly altered the expression of some immunityrelated genes in insect hosts (Xi et al, 2008;Zheng et al, 2011a;Yuan et al, 2015;Caragata et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…However, both the insects with newly acquired Wolbachia infection and those insects that have been infected by Wolbachia naturally for a long time, increase their resistance to pathogens (Kambris et al, 2009;Moreira et al, 2009;Pan et al, 2018). Furthermore, some studies, including our group, found that Wolbachia significantly altered the expression of some immunityrelated genes in insect hosts (Xi et al, 2008;Zheng et al, 2011a;Yuan et al, 2015;Caragata et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…A total of 33 097 genes could be annotated in the NR database [National Center for Biotechnology Information (NCBI) nonredundant protein sequences] by using DIAMOND v. 0.8.22 (with an e-value of 1 × 10 −5 ), covering 70.36% of the total assembled unigenes (47 034). Part of our assembly of genes could not be mapped to the NR database, likely linked to misassembly or a lack of representation in the database (Caragata et al, 2017).…”
Section: Gene Functional Annotationmentioning
confidence: 99%
“…Wolbachia are best known for their manipulation of host reproduction that serves to enhance their transmission through host populations (Zheng et al, 2011a;LePage et al, 2017;Beckmann et al, 2017), and it has also been shown that Wolbachia can influence host fitness traits, including physiology, immunity and pathogen interference (Hedges et al, 2008;Zug and Hammerstein, 2015;Ye et al, 2017;Ross et al, 2017;Teixeira et al, 2008). The influence of Wolbachia on fitness traits may be multidimensional, and a number of host genes and proteins modified by Wolbachia infection have been identified (Xi et al, 2008;Landmann et al, 2009;Caragata et al, 2017;Zheng et al, 2011b;Yuan et al, 2015;Christensen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%